Proses Pembuatan Pintu Kuwadi di PT. Sraya Bali Style Gianyar, Bali: - - I Putu Putra Suryadana; I Ketut Sidaarsa; I Nyoman Laba (Pusat Penerbitan LP2MPP ISI Denpasar, 2022)
This research aims to explain the form, manufacturing process and philosophy on kuwadi doors as elements of traditional Balinese architecture.This research was conducted at PT. Sraya Bali Style in the odd semester of the 2021-2022 school year. Research data is collected by conducting observations, interviews, documentation and library studi. The study was analyzed with a qualitatively transcribed approach. The expected results get an overview related to the shape, process of embodiment and philosophy of kuwadi door as one of the elements of traditional Balinese architecture. The author hopes this research can provide an overview in the form of science related to the existence of traditional Balinese architectural elements, as a foothold in the realization and knowledge of the younger generation (millennials) of Bali about the existence and preservation of traditional architecture that needs to be maintained and applied in relation to the embodiment guidelines that have existed since time immemorial.